2005
DOI: 10.1089/aid.2005.21.1066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HIV Type 1 Subtype C Full-Length gag Gene Sequences from India: Novel Observations and Plausible Implications

Abstract: Twenty-four HIV-1 gag genes from patients in India were sequenced and analyzed. All measured 1476-1491 nucleotides with an average of 1483 nucleotides in length. Phylogenetic analysis revealed a homogeneous epidemic of HIV-1 subtype C. Intragenotypic divergence of up to 6.6% was present. Fourteen novel conserved signature pattern residues were delineated for HIV-1 subtype C strains. Each of the 15 nucleocapsid (NC) basic residues was highly conserved p6 gag LXSLFG and PT/SAPP motifs were highly conserved excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…3). It may be pertinent to mention that a distinct Indian subclade was also recognized by our group earlier based on the full-length gag gene sequences form 25 Indian isolates of subtype C. 8 These findings imply that both structural as well as regulatory genes can be used for virus subtyping.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…3). It may be pertinent to mention that a distinct Indian subclade was also recognized by our group earlier based on the full-length gag gene sequences form 25 Indian isolates of subtype C. 8 These findings imply that both structural as well as regulatory genes can be used for virus subtyping.…”
mentioning
confidence: 52%
“…Substantial data are available on the genomic diversity of structural genes (env/gag) of almost all the important subtypes of HIV-1 [5][6][7] including our own recent report on full-length gag gene sequences from India. 8 In recent years, however, due emphasis has been given to the regulatory nef gene that plays a crucial and multiple role in HIV infection. 9,10 The nef gene was first identified as an open reading frame (ORF), which partially overlaps with the 3Ј-long terminal repeat (LTR) of HIV-1, and was reported to have a negative effect on viral replication, hence the name "negative factor" or "nef."…”
Section: Introductionmentioning
confidence: 99%
“…Subtype A strains were found to be related to Central and East African subtype and subtype B strains obtained from Manipur were related to subtype B sequences circulating in Thailand [13]. However, recent studies have clearly shown that subtype C strains have displaced subtype B in the IV drug users in that part of India [7,15].…”
Section: The Indian Scenariomentioning
confidence: 98%
“…Amino acid signature sequences were identified using VESPA. 14 We assessed whether CRF07_BC sequences from Beijing had amino acid substitutions characteristic of their origin. We found that the CRF07_BC Beijing sequence differed at five amino acids from that of other CRF07_BC sequences.…”
Section: Analysis Of Gag-pol Gene Of Beijing Bmentioning
confidence: 99%